1995
DOI: 10.1111/j.1460-9592.1995.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of apnoea in anaesthetized children required for desaturation of haemoglobin to 95%: comparison of three different breathing gases

Abstract: In this study, we compared three gas compositions to determine if the duration of apnoea for SpO2 to decrease is proportionate to the oxygen fraction of the gas prior to apnoea. Twenty-five patients ASA physical status 1-2 aged two months to 12 years were included in the study. Anaesthesia was induced via a mask with 5% sevoflurane and 66% N2O in oxygen. After paralysis with vecuronium (0.12 mg.kg-1, i.v.) the trachea was intubated and anaesthesia was maintained with sevoflurane and N2O in oxygen. When cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…A reduced tolerance to apnea, which may result from different factors such as increased oxygen demand, reduced functional residual capacity and increased closing capacity and very limited cooperation during the preoxygenation are related to age. Neonates and infants may develop hypoxemia (SpO 2 < 90%) before full neuromuscular blockade is accomplished[567] and rapid desaturation may be more dramatic in severely ill-children.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced tolerance to apnea, which may result from different factors such as increased oxygen demand, reduced functional residual capacity and increased closing capacity and very limited cooperation during the preoxygenation are related to age. Neonates and infants may develop hypoxemia (SpO 2 < 90%) before full neuromuscular blockade is accomplished[567] and rapid desaturation may be more dramatic in severely ill-children.…”
Section: Discussionmentioning
confidence: 99%
“…Dixon et al menunjukkan manfaat serupa pada 3 randomized controlled trial pada pasien dengan body mass index lebih besar dari 40 yang mana diposisikan pada posisi head up 30 derajat. 5,21,22,23,24 Sebaliknya posisi Trendelenburg (kepala 30 derajat lebih tinggi dari kaki) juga meningkatkan preoksigenasi dan mungkin berguna pada pasien yang tidak dapat terikat pada bahu, yang diimobilisasi karena kemungkinan spinal injury.…”
Section: Metodeunclassified
“…But the thresholds set by those investigators have been found to have relatively low sensitivity/specificity in diagnosing mild SDB such as upper airway resistance syndrome (13,14), which is known to occur without a large decline in SpO 2 (14–16). As younger children are more likely to exhibit a SpO 2 decline over the same duration of apnea/hypopnea than older children and adults (16–18), we thought that slight SpO 2 decline during sleep might be detected more easily in young children with mild SDB.…”
Section: Introductionmentioning
confidence: 99%